IDDF2018-ABS-0174 Fecobionics: novel defecatory function test. (June 2018) - Chen, Ssu Chi; Futaba, Kaori; Leung, Wing Wa; Wong, Cherry; Mak, Tony; Ng, Simon; Gregersen, Hans
Abstract : Background: Defecation is a complex process. Defecatory disorders may be assessed using rectal balloon expulsion test (BET), high-resolution anorectal manometry (HR-ARM) and defecography. We have developed a Fecobionics device that integrates several current tests 1 to assess pressures, orientation and bending all at once by the patient bedside. The Fecobionics probe is 10 cm long, 12 mm in diameter with 8 cm long inflatable bag and pressure sensors at each end. It contains two gyroscopes to measure the orientation and bending during defaecation. Aim: To characterise physiological expulsion parameters in asymptomatic subjects using Fecobionics. Methods: Fecobionics was inserted into the rectum and subjects were asked to sit on a commode. The bag was filled with fluid until subjects had the sensation to defaecate. Patients were asked to expel the Fecobionics. Time to expulsion, pressures and bending angles were assessed during the expulsion. This was compared to conventional 5=BET and HR-ARM. Results: Eight subjects (6F/2M, 50 years (25–77)) were assessed. Defaecation urge was felt at 32±=. Five subjects expelled Fecobionics in one attempt. The expulsion time for Fecobionics and BET were 32.2±6.3 and 15.7±3.3 s respectively (p<0.05). Linear association was found between the duration of Fecobionics and BET expulsions (R 2 =0.48). During Fecobionics expulsion all pressure sensors showed elevated pressures. The front end pressure reached 20–50 cm/H2 O above baseline rectal pressure during anal canal passage. Rear end pressure was 28.9±4.6 cm/H2 O before expulsion to a maximum pressure of 144.7±15.7 cm/H2 O during the expulsion. Defecations could be subdivided into five distinct phases based on the front and rear pressures and their pressure difference 1 . The bending angle was 137.2±9.6 o before defaecation, 145.3±5.0 o at maximum contraction, and 178.7±0.9 o during anal passage (p<0.05); indicative of changes in the anorectal angle. Conclusions: It was possible to obtain reliable data under physiological conditions using Fecobionics. Five defecatory phases could be defined by the pressure signature. Orientation and bending could also be assessed.